Combating Deforestation through REDD+ in the Brazilian Amazon: - Anthony Hall (Sustentabilidade em Debate, 2013)
Brazil is developing a number of REDD+ schemes in Amazonia that offer economic incentives to discourage deforestation and promote conservation. Building upon longer traditions of forest preservation and sustainable development in the region, REDD+ could be said to embody elements of a new ‘social contract’ that underpins resource governance, based on mutual obligations, rights and responsibilities. This will have to be founded on negotiated agreements among major stakeholders; namely, central and state governments, the NGO sector, private business interests and local beneficiary populations. Despite its embryonic nature and having to face major challenges of implementation and scaling up, REDD+ could offer the beginnings of a fresh paradigm in environmental policy based on a social contract that could help sustain low rates of forest loss in future.